Discovery of novel coumarin derivatives as potent and orally bioavailable BRD4 inhibitors based on scaffold hopping - Zhimin Zhang; Lili Gu; Beibei Wang; Wenhai Huang; Yanmin Zhang; Zhen Ma; Shenxin Zeng; Zhengrong Shen (Taylor & Francis Group, 2019)
The bromodomain and extra-terminal (BET) bromodomains, particularly BRD4, have been identified as promising therapeutic targets in the treatment of many human disorders such as cancer, inflammation, obesity, and cardiovascular disease. Recently, the discovery of novel BRD4 inhibitors has garnered substantial interest. Starting from scaffold hopping of the reported compound dihydroquinazolinone (PFI-1), a series of coumarin derivatives were designed and synthesised as a new chemotype of BRD4 inhibitors. Interestingly, the representative compounds 13 exhibited potent BRD4 binding affinity and cell proliferation inhibitory activity, and especially displayed a favourable PK profile with high oral bioavailability (F = 49.38%) and metabolic stability (T1/2 = 4.2 h), meaningfully making it as a promising lead compound for further drug development.